(untitled) (Research, Society and Development, 2020)
The objective was to analyze the use of Personal Protective Equipment (PPE’s) in the protection and prevention of occupational accidents involving biological risks to which health professionals are exposed. The study consisted of an integrative review, using articles published in the last eight years through the search for the keywords: "Personal Protection Equipment", "Occupational Health, "Occupational Risks" and "Health Personnel" in the LILACS and MEDLINE electronic databases. It was evidenced that the PPE used in the health area are diverse, as well as their indications, advantages, disadvantages and modes of use. There was a strong relationship between the use and reduction of the risk of accidents due to biological exposure, and adherence was influenced by the quality and availability of them in the services. Equipment such as N95 masks, face shields and the use of double pairs of gloves demonstrated greater effectiveness compared to other PPE’s of their categories. Studies have also shown that the correct technique of placing and removing these equipments is decisive to predict the risk of contamination. Therefore, PPE are effective in preventing accidents, although their poor adherence and use are barriers to occupational safety, requiring reformulations and regulatory actions of a socio-pedagogical nature.